A Systematic Review of Transesophageal Echocardiography‐Induced Esophageal Perforation. Issue 8 (9th July 2013) - Sainathan, Sandeep; Andaz, Shahriyour
<x xml:space="preserve">Abstract</x> A systematic review of transesophageal echocardiography (TEE)‐induced esophageal perforation was done using the MEDLINE (PubMed and OVID interfaces), Google Scholar and EMBASE databases. Thirty‐five cases of esophageal perforation from 22 studies were analyzed. TEE‐induced esophageal perforation occurs in elderly female patients, predominantly in an intra‐operative setting. Thoracic esophagus is the most commonly involved segment, especially, when TEE is performed intra‐operatively. Majority of the esophageal perforations occur in cases with a perceived low risk or smooth TEE exam and thus, screening for high risk factors may not eliminate the occurrence of a perforation. A delayed detection of perforation occurs when it is a thoracic esophageal perforation, performed intra‐operatively and when there are no known preoperative risk factors. Shock during the detection of the perforation is associated with mortality. Majority of the perforations can be repaired primarily.